Differential geometry of the Z3-graded quantum supergroup GLq,j(1|1) - Celik, S.; Yasar, E. (ELSEVIER SCIENCE BV, 2011)
In this work, differential geometry of the Z(3)-graded quantum supergroup GL(q,j)(1 vertical bar 1) is constructed. The corresponding quantum Lie superalgebra is obtained. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Z(3)-graded quantum supergroup; Super-Hopf algebra; Z(3)-graded quantum superplane; Quantum Lie superalgebra; CALCULUS; DEFORMATION; Mathematics; Physics